Ascorbic acid enhances the treatment efficacy of tetracycline against experimentally infected Aeromonas hydrophila - Omeje, V; Okolo, CC; Kolndadacha, OD; Ezema, C (Journal of the Hellenic Veterinary Medical Society, 2025)
Combinations of two or more pharmaceuticals are sometimes used to achieve efficient treatment of an ailment. The objectives of this study were to evaluate the synergistic action of ascorbic acid combined with tetracycline in the treatment of Aeromonas hydrophila infection. A total of 210 apparently healthy 2-month-old uniformly sized Clarias gariepinus with a mean weight of 24.65±2.78 g were used in the study. The fish were randomly assigned to seven treatment groups (A, B, C, D, E, F and G), each in triplicate. The fish in group A were the uninfected controls, while those in groups B to G were infected with the bacterium and were either treated or not treated with tetracycline, and their diets were either supplemented with ascorbic acid or not. Growth, survival, hematological parameters, serum chemistry responses were investigated as bioindicators of health status. Infected fish deprived of L-ascorbic acid presented lower growth and survival rates. Hemorrhages, skin and fin erosions and skeletal deformities were some of the lesions observed. There were significantly (P<0.05) lower red blood cell counts and hemoglobin; significantly higher (P<0.05) total leucocyte counts; total protein, globulin and albumin; and elevated A/G ratios, also significantly higher alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and urea levels when compared with the group without ascorbic acid supplementation. This study suggested that ascorbic acid supplementation at 100 and 200 mg/kg is recommended in the diet of C. gariepinus to potentiate the action of tetracycline in the treatment of A. hydrophila infection.